Estudo das infecções intramamárias em cabras do município de queimadas – pb e seu impacto na saúde pública - Oliveira, Pedro Thiago Barbosa de (2023)
The state of Paraíba is nationally known for the production of goat milk. Mastitis is one of the most frequent diseases in dairy herds, which can bring losses to animal welfare, increase production costs and promote risks to human and animal health. This disease is usually caused by bacteria, which must be precisely identified to promote an adequate treatment. The aim of this study was to identify the species of bacteria found in the mammary glands of goats belonging to herds in Queimadas-PB, using the MALDI-TOF MS technique, and to carry out sensitivity tests on the bacteria found. Milk samples were aseptically collected from 57 animals from 8 herds, totaling 113 mammary halves, which were taken to the laboratory for lactoculture. After identification, the bacterial isolates were submitted to sensitivity tests by disk diffusion. In all the farms visited, the milking system used was hand milking. All the farmers wash their hands before milking. On all 8 properties there was a milking platform. Only one participating performs the dark-bottom cup test and pre-dipping, while post-dipping was recorded by 4 farmers. Bacterial growth was found in samples from 15 of the 113 mammary halves collected, where Staphylococcus caprae, Staphylococcus epidermidis, Staphylococcus lugdunensis and Micrococcus luteus species were identified. The bacterial isolates were largely susceptible to the antibiotics tested, however, one multidrug-resistant strain was found. The dairy goat herds in the municipality of Queimadas-PB are raised in systems of incipient technification. In these herds, there is occurrence of subclinical mastitis. The bacteria found were very sensitive to a good variety of antimicrobials, however, resistant strains were found.